Relationship between upper-body strength and bat swing speed in high-school baseball players - Miyaguchi, K.; Demura, S. (The Journal of Strength and Conditioning Research, 2012)
This study aimed to clarify the relationship between upper-body strength and bat swing speed in high-school baseball players and to examine the physical characteristics of home run hitters (sluggers). The subjects were 30 male high-school baseball players with national tournament experience at the Koshien Stadium. Bat swing speed exerted by full effort was measured with a microwave-type speed-measuring instrument. One-repetition maximum (1RM) of a bench press (BP), BP power (bench power) using a light load (30 kg), and isokinetic chest press (0.4, 0.8, 1.2 m/s) were measured as upper-body strength. The relationships between bat swing speed and upper-body strength values were examined. Additionally, the t-test was used to reveal the mean differences between 14 home run hitters (group A) and 16 mediocre hitters (group B) for each measurement value. The bat swing speed showed significant and middle correlations with the 1RM BP (r = 0.59), bench power (0.41), and isokinetic chest press (0.48-0.55). Group A had significantly higher values in bench power and isokinetic chest press (high-speed) per kilogram of body weight than did group B. The swing speed showed significant correlations (r = 0.62) with the 1RM BP in group B but not in group A. In conclusion, to improve the hitting power of high-school baseball players, it may also be important to develop bench power with light loads in addition to 1RM BP.